2004
DOI: 10.1111/j.1572-0241.2004.30313.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Helicobacter Pylori Infection and the Status of Gastric Acid Secretion in Patients with Barrett's Esophagus in Japan

Abstract: H. pylori infection may play a protective role in the development of Barrett's esophagus, especially in the development of LSBE in Japan. Gastric acid hypersecretion may be concerned with the development of Barrett's esophagus in addition to the absence of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 44 publications
5
48
0
4
Order By: Relevance
“…The presence of H pylori is believed to protect against GERD and associated long-segment BE (36)(37)(38). In our series, BE patients were less likely to be H pylori-positive than were non-BE patients (10% versus 42.5%, respectively; P Ͻ 0.05), confirming the potential protective role of H pylori.…”
Section: Discussionsupporting
confidence: 70%
“…The presence of H pylori is believed to protect against GERD and associated long-segment BE (36)(37)(38). In our series, BE patients were less likely to be H pylori-positive than were non-BE patients (10% versus 42.5%, respectively; P Ͻ 0.05), confirming the potential protective role of H pylori.…”
Section: Discussionsupporting
confidence: 70%
“…As found in other studies, a study from Japan showed that H. pylori infection may play a protective role in the development of BE (especially LSBE), although the number of patients evaluated was limited [90]. The same group proposed that the preservation of gastric acid secretion might be important for the development of adenocarcinoma at the EGJ (including EAC) in Japanese people, irrespective of the H. pylori infection status [91].…”
Section: H Pylori Infection and Carcinogenesismentioning
confidence: 78%
“…This has been found in published studies. 14,17,22,2 Furthermore, there is a stronger negative association between H. pylori infection and endoscopically-demonstrated reflux oesophagitis than between H. pylori and GORD without macroscopic oesophagitis. [26][27][28] …”
Section: H Pylori and Gord Complications In East Asiamentioning
confidence: 99%
“…This is indeed the case: studies from these countries consistently show a strong negative association. [12][13][14][15][16][17] The effect of cytokine gene polymorphism…”
Section: H Pylori and Gord Complications In East Asiamentioning
confidence: 99%